Firmly standing three-dimensional radial junctions on soft aluminum foils enable extremely low cost flexible thin film solar cells with very high power-to-weight performance. (November 2018) - Sun, Xiaolin; Zhang, Ting; Wang, Junzhuan; Yang, Fan; Xu, Ling; Xu, Jun; Shi, Yi; Chen, Kunji; Roca i Cabarrocas, Pere; Yu, Linwei
Abstract: Flexibility and power-to-weight (PTW) ratio are the key factors for promoting wearable or portable solar cell applications. Planar hydrogenated amorphous silicon (a-Si:H) thin films deposited directly on soft aluminum foils (AF) are usually subject to easy cracking and delamination due to the mechanical instability on AF surface. Here, an exceptionally robust three-dimensional (3D) construction of a-Si:H radial p-i-n junction solar cells on soft supermarket-available AF of 15 µm thick is reported, where the discrete and firmly standing Si nanowire (SiNW) cores, grown and rooted on the soft AF surface, frame up a 3D architecture that protects the protrusive photo-active radial junctions from the unstable a-Si/Al bottom layer. An excellent flexibility and integrity of the 3D a-Si:H radial junctions have been achieved, even under bending to radius of 5 mm. Remarkably, without any diffusion barrier protection, a power conversion efficiency of 5.6% has been recorded, with an open-circuit voltage of 0.71 V and photo-current density of 14.2 mA/cm 2, leading to a high PTW ratio of > 1300 W/kg. Importantly, the overall fabrication cost can be largely slashed off, by 46% compared to conventional a-Si:H solar cells, as the need for a bottom TCO contact/texturing layer, for a back-reflection coating and for a glass/polymer substrate are all exempted. Graphical abstract: fx1 Highlights: Firmly standing radial junctions enables robust flexible thin film solar cells on soft aluminum foils. 3D geometric engineering dissipates the strains and suppress delamination, while achieving strong light trapping. Achieving a record high power-to-weight ratio of > 1300 W/kg. Overall fabrication cost decreases by 46% thanks to the conductive and reflective aluminum foil substrate.